The description of condyle position in disc displacement with reduction using Cone Beam Computed Tomography 3D radiographic analysis - Rahmayani, Liana; Kurnikasari, Erna; Rikmasari, Rasmi (Universitas Padjadjaran, 2009)
One of the temporomandibular joint disorders that mostly occurs is disc displacement with reduction. Disc displacement that causes the displacement of condyle position can be evaluated by using radiograph. The Cone Beam Computed Tomography (CBCT-3D) is a radiograph equipment which is able to capture the condyle position from many directions. This research was aimed to see the condyle position in patients with disc displacement with reduction symptoms. This research was conducted to 11 patients with symptoms of disc displacement with reduction and 3 patients without symptoms of disc displacement with reduction as the counterpart. What was conducted to the sample was the radiographic imaging using CBCT-3D radiography, followed by measuring the joint space distance in the sagittal and coronal directions. The result of the research was analyzed using the T-test. Statistically, the result of the test showed a significant difference ( = 0.05) between patients with disc displacement with reduction symptoms and the patients without symptoms, in sagittal and coronal views. The conclusion led to the difference in condyle positions in patients with the disc displacement with reduction and patients without the symptoms which meant there was a condyle position displacement that caused the distance alteration in joint space in sagittal and coronal directions.